2001
DOI: 10.1177/0310057x0102900609
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial Comparing Two Laryngeal Mask Airway Insertion Techniques

Abstract: This study was undertaken to compare laryngoscopic-guided LMA insertion with a standard insertion technique. A total of 149 patients undergoing elective general surgical and orthopaedic procedures were randomly divided into two groups. Study endpoints included ease of insertion, haemodynamic changes, local trauma bleeding, and postoperative sore throat. There were no statistically significant differences found. The laryngoscope may aid laryngeal mask airway insertion in some circumstances. FIGURE 1: Blood pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 10 publications
(12 reference statements)
0
14
0
2
Order By: Relevance
“…Of note, there were no incidences of sore throat when cuff pressures were <40 cmH 2 O, a pressure unlikely to exceed the pharyngeal perfusion pressure (15). In line with previous studies, the insertion as well as the removal technique of the LMA did not affect the development of sore throat (16–18).…”
Section: Discussionmentioning
confidence: 97%
“…Of note, there were no incidences of sore throat when cuff pressures were <40 cmH 2 O, a pressure unlikely to exceed the pharyngeal perfusion pressure (15). In line with previous studies, the insertion as well as the removal technique of the LMA did not affect the development of sore throat (16–18).…”
Section: Discussionmentioning
confidence: 97%
“…But they have several disadvantages like dislocation of the arytenoid cartilages, unsatisfactory positioning, and need for laryngoscopy. [3–5] Experience with newer supraglottic devices has shown that these can be just “pushed in” to their correct final position when steered along the palate, without the need for digital intraoral manipulation.…”
Section: Discussionmentioning
confidence: 99%
“…In pediatric anesthesia various LMA insertion techniques are described and used in clinical practice (Table 2) (10–17). Most differ in the cuff volume at the time of LMA insertion.…”
Section: Discussionmentioning
confidence: 99%